2012
DOI: 10.1093/her/cys108
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing lifestyles for men regarded as 'hard-to-reach' through top-flight football/soccer clubs

Abstract: This study assessed the effect of a 12-week behavioural intervention delivered in and by English Premier League football/soccer clubs, and its influence on lifestyle behaviours, in men typically regarded as hard-to-reach. One hundred and thirty men aged 18 years or older engaging in the programme self-reported data on optimal lifestyle behaviours (OLBs) (physical activity, diet, smoking and alcohol consumption) at pre- and post-intervention. Logistic regression models were used to predict the likelihood of OLB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
56
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 45 publications
1
56
0
Order By: Relevance
“…However, the potential of professional sporting organisations to attract men to health promotion activities is now widely recognised. [36][37][38][39][40][41] A National Institute for Health Research (NIHR) Public Health Research programme-funded randomised controlled trial (RCT) (09/3010/06) 42 provided evidence of the success of professional football clubs in engaging men in a weight loss and healthy living programme [Football Fans in Training (FFIT)] and supporting them to lose weight [42][43][44] and to make other positive changes to their health and behaviours up to 12 months after baseline measurement. The present study reports on the follow-up study (to 3.5 years post baseline measurement) of participants in the RCT of the FFIT programme at 13 of the top professional football clubs in Scotland (ISRCTN32677491).…”
Section: Men and Weight Managementmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the potential of professional sporting organisations to attract men to health promotion activities is now widely recognised. [36][37][38][39][40][41] A National Institute for Health Research (NIHR) Public Health Research programme-funded randomised controlled trial (RCT) (09/3010/06) 42 provided evidence of the success of professional football clubs in engaging men in a weight loss and healthy living programme [Football Fans in Training (FFIT)] and supporting them to lose weight [42][43][44] and to make other positive changes to their health and behaviours up to 12 months after baseline measurement. The present study reports on the follow-up study (to 3.5 years post baseline measurement) of participants in the RCT of the FFIT programme at 13 of the top professional football clubs in Scotland (ISRCTN32677491).…”
Section: Men and Weight Managementmentioning
confidence: 99%
“…46 Figure 1 provides an overview of the design of the FFIT RCT conducted in 2011/12; further details are provided elsewhere. 43,44 This was a pragmatic trial, with weight loss at 12 months as the primary outcome, in which 747 men (aged 35-65 years with an average BMI of ≥ 28 kg/m 2 ) were randomly allocated either to the FFIT RCT intervention group (n = 374) or to a waiting list comparison group (n = 373) following baseline measurements at the 13 participating football clubs. The baseline measurements demonstrated that the programme successfully engaged men from across the socioeconomic spectrum 43 whose excess body weight put them at a high risk of ill health.…”
Section: Men and Weight Managementmentioning
confidence: 99%
See 3 more Smart Citations